(untitled) (Chittagong University Journal of Biological Sciences, 2024)
The purpose of the present study was to explore whether there is any relation between adolescent adjustment and depression of students in relation to types of institution, types of medium and family structure. This study was conducted on 160 respondents of age 10-19 years, selected purposively from different areas of Chittagong district. The Bangla version of adolescent adjustment scale (Sarkar & Khanam,2008) and Depression scale (Rahman & Uddin,2005) were used to measure adjustment and depression of adolescents. The findings of the present study showed that mean score of adolescent’s personal, social adjustment and depression was 63.31, 44.55 and 81.24, respectively. Mean of college students was more than school students, mean score of Bangla medium students was more than English medium students, and mean score of joint family adolescent was more than nuclear family students. In addition, there was significant interaction effect between types of medium and family structure, among types of institution, types of medium and types of family structure on personal adjustment. Similar significant interaction effect on depression was also observed among the responders. Detailed statistical analyses furthermore showed significant positive correlation between personal and social adjustment, significant negative correlation between personal adjustment and depression, social adjustment and depression. The results have been constructed in the light of past studies and the findings of the present study have both theoretical and practical implications. The Chittagong Univ. J. B. Sci. 9(1&2):125-140,2019